Analisis Makna Pada Puisi “Sajak-Sajak Empat Seuntai” Karya Sapardi Djoko Damono Menggunakan Pendekatan Semiotik - Caca Hidayat (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
Poetry is a literary work which contains expressions of the author poured into written form with implied meaning so the readers can interpret the results of the written work freely. This study used qualitative method with semiotic approach such as: 1) to describe the meaning of the poems 2) to know the number of icons, 3) to know the number of indexes, 4) to know the number of symbols. The results showed (1) this poem has a deep meaning about the closeness of a human being with his creator, so that at first he was far away but after trying to keep getting closer he felt a calmness, which he had never felt before, (2) there was a choice of diction that used icons, indexes, and symbols written by Sapardi Djoko Damono in expressing the meaning of the poem "Four Seuntai Poems" indirectly to the reader and (3) In the poem "Four Seuntai Poems" written by Sapardi Djoko Damono like as (a) four icons consisting of the words sent, delivered, void and breaking through, (b) three indexes consisting of forbidden words, understanding, reaching, (c) seven symbols consisting of the words house, sea, fire, garden, sky, lost, memory.